THE EFFECT OF PROBLEM BASED LEARNING (PBL) AND DIRECT INSTRUCTION METHOD (DIM) ON THE STUDENTS’ ACHIEVEMENT IN READING COMPREHENSION AT SMA NEGERI 1 DOLOK PARDAMEAN - evanansi Marpaung (Edumedia : Jurnal Keguruan dan Ilmu Pendidikan, 2020)
This study attempted to find out the effect of PBL and DIM on the Students’ Achievement in Reading Comprehension at SMA Negeri 1 Dolok Pardamean. This research applied quantitative method. To analyze the data, the writer found out the mean, standard deviation, validity and reliability of the test. After calculating them, the writer used t-test to know the effect of PBL and DIM on the students’ achievement in reading comprehension. The result revealed that there was any effect of PBL and DIM on the students’ achievement in reading comprehension that showed from the result: μX>μY (67.07 > 50.47) and tobs > ttable 75.45 > 0.003, and in DIM64.90 > 50.47 and tobs > ttable (60.12 > 0.003). From the result of analysis, the effect of PBL is more significant than the effect of DIM on the Students’ Achievement in Reading Comprehension. So, PBL should be applied in teaching reading comprehension.